Deoxyxylulose 5-Phosphate Synthase Controls Flux through the Methylerythritol 4-Phosphate Pathway in Arabidopsis. Issue 4 (1st July 2014) - Wright, Louwrance P.; Rohwer, Johann M.; Ghirardo, Andrea; Hammerbacher, Almuth; Ortiz-Alcaide, Miriam; Raguschke, Bettina; Schnitzler, Jörg-Peter; Gershenzon, Jonathan; Phillips, Michael A.
Abstract : 1-Deoxyxylulose 5-phosphate synthase is the controlling enzyme of plastid isoprenoid precursor biosynthesis in Arabidopsis. Abstract: The 2-C-methylerythritol 4-phosphate (MEP ) pathway supplies precursors for plastidial isoprenoid biosynthesis including carotenoids, redox cofactor side chains, and biogenic volatile organic compounds. We examined the first enzyme of this pathway, 1-deoxyxylulose 5-phosphate synthase (DXS ), using metabolic control analysis. Multiple Arabidopsis ( Arabidopsis thaliana ) lines presenting a range of DXS activities were dynamically labeled with 13 CO2 in an illuminated, climate-controlled, gas exchange cuvette. Carbon was rapidly assimilated into MEP pathway intermediates, but not into the mevalonate pathway. A flux control coefficient of 0.82 was calculated for DXS by correlating absolute flux to enzyme activity under photosynthetic steady-state conditions, indicating that DXS is the major controlling enzyme of the MEP pathway. DXS manipulation also revealed a second pool of a downstream metabolite, 2-C-methylerythritol-2, 4-cyclodiphosphate (MEcDP ), metabolically isolated from the MEP pathway. DXS overexpression led to a 3- to 4-fold increase in MEcDP pool size but to a 2-fold drop in maximal labeling. The existence of this pool was supported by residual MEcDP levels detected in dark-adapted transgenic plants. Both pools of MEcDP are closely modulated by DXS activity, as shown by the fact that the concentration control coefficient of DXS was twice as high for MEcDP (0.74) as for 1-deoxyxylulose 5-phosphate (0.35) or dimethylallyl diphosphate (0.34). Despite the high flux control coefficient for DXS, its overexpression led to only modest increases in isoprenoid end products and in the photosynthetic rate. Diversion of flux via MEcDP may partly explain these findings and suggests new opportunities to engineer the MEP pathway.